Role of Algae and Cyanobacteria in Crop Protection - Asritha, Ch.; Ramesha, N. M.; Satwika, Maharaj (Chronicle of Bioresource Management, 2024)
As the human population grows, so does the need for increased food production. Traditional agricultural practices, especially synthetic pesticide use, are heavily criticized for their environmental impact and face significant public opposition. There is a pressing need for sustainable alternatives that are safe for both humans and ecosystems. Additionally, resistance to current pesticides poses a major challenge, making them less effective over time. Scientists are thus focusing on developing novel pesticidal compounds from unexplored chemical classes, with distinct toxicities and modes of action. These new compounds aim to minimize adverse interactions with existing treatments, offer better control over agricultural pests, and address public concerns about safety. The ultimate goal is to create a generation of eco-friendly, sustainable pesticides that protect crops while preserving ecological balance, representing a vital shift toward environmentally conscious agriculture in the face of rising food demands.